Quadratic equations can be solved using several methods; one of them, is by using quadratic formula
The solution to [tex]5x^2 - 8x + 5 = 0[/tex] is: [tex]x = \frac{4 + 3i}{5}, x = \frac{4 - 3i}{5}[/tex]
The equation is given as:
[tex]5x^2 - 8x + 5 = 0[/tex]
The quadratic formula is:
[tex]x = \frac{-b \± \sqrt{b^2 - 4ac}}{2a}[/tex]
In the given equation;
[tex]a = 5\\b = -8\\c = 5[/tex]
So:
[tex]x = \frac{-(-8) \± \sqrt{(-8)^2 - 4 \times 5 \times 5}}{2 \times 5}[/tex]
[tex]x = \frac{8 \± \sqrt{-36}}{10}[/tex]
Expand
[tex]x = \frac{8 \± \sqrt{36} \times \sqrt{-1}}{10}[/tex]
[tex]x = \frac{8 \± 6 \times \sqrt{-1}}{10}[/tex]
In complex numbers;
[tex]i = \sqrt{-1}[/tex]
So, we have:
[tex]x = \frac{8 \± 6 \times i}{10}[/tex]
[tex]x = \frac{8 \± 6i}{10}[/tex]
Simplify
[tex]x = \frac{4 \± 3i}{5}[/tex]
Split
[tex]x = \frac{4 + 3i}{5}, x = \frac{4 - 3i}{5}[/tex]
Hence, the solution to [tex]5x^2 - 8x + 5 = 0[/tex] is: [tex]x = \frac{4 + 3i}{5}, x = \frac{4 - 3i}{5}[/tex]
Read more about quadratic formulas at:
https://brainly.com/question/9701183